The Oregon Trail. The Final steps [videorecording (VHS)] - Boettcher, Steven J.; Trinklein, Michael J. (Films for the Humanities, 1993)
Follows the final journey on the Oregon Trail to the Willamette Valley. In addition to pointing out important sites en route, this program discusses the role of the British, 49ers along the Trail and conflict with Native Americans in the later years.